Direct fabrication of unsupported inclined aluminum pillars based on uniform micro droplets deposition - Zhang, Daicong; Qi, Lehua; Luo, Jun; Yi, Hao; Hou, Xianghui (Elsevier, 2017)
In order to investigate forming directly complex parts without support materials or structures by uniform micro droplets deposition technique, the present work focus on fabricating the unsupported inclined aluminum pillars through offset deposition. An experimental system is developed to produce and deposit uniform molten aluminum droplets. A model is introduced to describe the inclined angle of the droplet deposition at different offset ratios. A one dimensional heat transfer model is proposed to help select the initial temperature parameters of the impinging droplet and the previous solidified droplet to ensure that the fusion occurs. No melting, partial melting and excessive melting region at different offset ratios are determined. The correspondence between offset ratio and inclined angle is considered to be a simple cosine function, and the hypothesis is verified by experiments. The influence of deposition error on an inclined angle of pillars is studied. Internal microstructure of droplet fusion is observed in order to ensure good metallurgical bonding. All of these studies show the feasibility of fabricating directly unsupported inclined aluminum pillars in the limited angle range by using uniform micro droplets.